BILINGUAL CHILDREN STORY BOOK : A FUNCTIONAL LINGUISTIC PERSPECTIVE OF LEARNING ENGLISH - Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2012)
Indonesian children are born as bilingual even multilingual children because Indonesia is a rich country having many different cultures. As one of cultural products, language can be learnt through various ways, one example is by reading children storybook. Language use is always socially and culturally situated. Learning English is a process of tranforming linguistics entities into knowledge implanted in children’s brain. It is through language that school subjects are taught and through language that students’ understanding of concept is displayed and evaluated in school context. Key words: bilingual, multilingual, learning, socially and culturally situated.